SECURE KNOWLEDGE MANAGEMENT: CONFIDENTIALITY, TRUST AND PRIVACY - Akhriza, Tubagus Mohammad (DINAMIKA DOTCOM, 2010)
Knowledge is one of the most important assets for an organization or a company. The knowledge in a company is the intellectual capital which could make the company keeps alive and competitive. As an important asset, the companyâs knowledge should be managed securely. In this paper, the author limits the discussion of the aspect of secure knowledge management to confidentiality, trust and privacy. For confidentiality, author discusses Role Based Access Control (RBAC) and Usage Control (UCON). Then we move to discuss the trust management and negotiation and stress the topic to trust negotiation (TN). Finally the author discusses about the privacy management. The conclusion is because the knowledge management is an important asset of organization as the intellectual capital, so security has to be incorporated into the knowledge-management lifecycle especially on integrating security strategy with knowledge management and business strategies of an organization.